Occurrence and distribution of antibiotics and antibiotic resistance genes in water of Liaohe River Basin, China. Issue 5 (October 2022) - Gao, Hui; Zhao, Fuqiang; Li, Ruijing; Jin, Shuaichen; Zhang, Haibo; Zhang, Keyu; Li, Shisheng; Shu, Qin; Na, Guangshui
Abstract: Surface water environment is an important repository of antibiotics and antibiotic resistance genes (ARGs). It is of great significance to study the occurrence and distribution of antibiotics and ARGs in surface water environment. In this study, the Liaohe River Basin, China was taken as the study area, and the concentrations of antibiotics and ARGs in water were investigated by HPLC-MS/MS and HT-qPCR. The results showed that a total of 53 antibiotics of 6 types were detected in water, and the pollution level was at ND~331.64 ng/L, where PCG was the highest. Totally 164 ARGs and 10 mobile genetic elements (MGEs) were detected in the water, and the absolute abundances were at 2.18 × 10 4 ~3.95 × 10 7 copies/L and 1.82 × 10 5 –3.78 × 10 7 copies/L, respectively. The multidrug and aminoglycoside were the dominant ARG types. Amoxicillin, erythromycin, anhydroerythromycin and ofloxacin posed certain ecological risks for sensitive aquatic organisms. In spatial distribution, the pollution of antibiotics and ARGs in the Daliao River system was higher than that in the Liaohe River system. There was a significant positive correlation between total concentrations of antibiotics and total relative abundance of ARGs ( r  = 0.66, p  < 0.05). The co-occurrence of multiple antibiotics promoted the pollution and spread of ARGs. In addition, the total relative abundance of MGEs and ARGs showed a significant positive correlation ( r  = 0.946, p  < 0.01), and MGEs played an important role in the occurrence and evolution of ARGs in water. Graphical Abstract: ga1 Highlights: A variety of antibiotics and ARGs were detected in water of Liaohe River Basin. β-lactams and macrolides were the main antibiotics, and multidrug and aminoglycoside were the dominant ARGs. The pollution of AMX, ENR, AETM and OFL posed high ecological risks for sensitive aquatic organisms (algae). The distribution of antibiotics and ARGs showed obvious spatial distribution characteristics. The total concentration of antibiotics and the abundances of MGEs correlated positively with the abundances of ARGs.